2015
DOI: 10.1002/tcr.201500018
|View full text |Cite
|
Sign up to set email alerts
|

Carbyne: The Molecular Approach

Abstract: For the last 60+ years, the synthesis and study of cumulenes and polyynes have been the focus of a small, but dedicated, group of researchers. Many of the remarkable electronic, optical, and structural properties of cumulenes and polyynes had already been identified in the earliest reports. The molecular lengths achievable by the initial syntheses were, unfortunately, somewhat limited by synthetic methods available. For the past 15 years, we have worked toward expanding on the synthesis of cumulenes and polyyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 108 publications
(209 reference statements)
0
25
0
1
Order By: Relevance
“…These linear molecules have several interesting properties. For example, they can be used as molecular wires [31][32][33][34] as their conductivity is significantly better than the other possible form of linear carbon chains,p olyynes. [32,35,36] Strong s donors as end-capping groups of the cumulene chain give their radical speciesaremarkable stability, [26,32,[37][38][39][40] with someo ft hese radicals stable even to air.…”
Section: Introductionmentioning
confidence: 99%
“…These linear molecules have several interesting properties. For example, they can be used as molecular wires [31][32][33][34] as their conductivity is significantly better than the other possible form of linear carbon chains,p olyynes. [32,35,36] Strong s donors as end-capping groups of the cumulene chain give their radical speciesaremarkable stability, [26,32,[37][38][39][40] with someo ft hese radicals stable even to air.…”
Section: Introductionmentioning
confidence: 99%
“…Mono-and bis(imidazolidinium ethynyl) cations have also been synthesized from the reaction of an NHC with phenylethynyl bromide or 1,4-bis(bromoethynyl)benzene.C yclic voltammetry coupled with synthetic and structural studies showed that the dication is readily reduced to aneutral, singlet bis-1,4-([3]cumulene)-p-carboquinoid as ar esult of the paccepting properties of the capping NHCs.Extended cumulenes and polyynes have received much attention. Fore xample,T ykwinski and co-workers [1,2] and others [3] have used them as molecular wires and as linkers between the end caps of rotaxanes. [4] These extended linear carbon-atom chains are conjugated p-systems,w hich allows for communication across their length.…”
mentioning
confidence: 99%
“…Extended cumulenes and polyynes have received much attention. Fore xample,T ykwinski and co-workers [1,2] and others [3] have used them as molecular wires and as linkers between the end caps of rotaxanes. [4] These extended linear carbon-atom chains are conjugated p-systems,w hich allows for communication across their length.…”
mentioning
confidence: 99%
“…В работе [29] серия линий с волновыми числами в диапазоне 1700−2200 cm −1 приписывается колебаниям sp-гибридизованных цепочек в структуре углеродсеребряных композитов. В то же время, данная линия не встречается в спектрах углеродных цепочек с sp-гибридизацией, находящихся в растворе [30,31], и не предсказывается моделями, в которых рассчитывается спектр идеальных цепочечных структур, стабилизированных различными радикалами [32]. Все это позволяет предположить ее связь с деформацией структуры цепочек.…”
Section: Pda Crystalunclassified